The Late presenting Bochdalek hernia; A Case report and review of literature - Imanzadeh, Farid; Tehrani Fateh, Sepand; Alimoghadam, Shaya; Dara, Naghi; Rouzrokh, Mohsen; Hosseini, Amirhossein (Student Research in Translational Medicine, 2021)
We report a 22-month-old boy who referred due to nausea, vomiting, abdominal pain and watery non-bloody diarrhea and after thorough evaluation, a large defect in the left postero-lateral side of diaphragm and presence of bowel loops, spleen, stomach and left lobe of liver in the left hemi-thorax were detected. So, he was operated and managed with the impression of Bochdalek hernia. We have also reviewed the similar case reports in the past 10 years, briefly, in order to map the presentations and clinical course of cases with Bochdalek hernia which were diagnosed late, for giving physicians a better insight on this issue.